2021
DOI: 10.1021/acscatal.0c05544
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Spatial Effect from Atomically Dispersed Co Anchoring on Subnanometer Ru Cluster for Enhanced N2-to-NH3 Conversion

Abstract: Simultaneously achieving a low activation barrier with weak binding of intermediates on a heterogeneous catalyst for the enhancement of catalytic performance under mild conditions remains a great challenge, especially for N2-to-NH3 conversion. Herein, for the first time, we report a new strategy via integrating vacuum-freeze-drying and high-temperature pyrolysis technologies to design atomically dispersed Co deposits onto the surface of Ru tiny subnanoclusters (TCs). The special structure of this catalyst can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…For example, Jiang et al designed an atomically dispersed Co deposit onto the surface of Ru tiny sub-nanoclusters (Co 1 Ru TCs). 43 According to the EPR spectra, the g value (2.56) of Co 1 Ru TCs could be ascribed to the unpaired electron in the orbital of Co II and Ru III . To explore the effect of electronic interaction between the atomically dispersed Co and Ru clusters, dual atomically dispersed Co and Ru (denoted as Co 1 Ru DAs) were also prepared.…”
Section: Other Applicable Characterization Techniquesmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Jiang et al designed an atomically dispersed Co deposit onto the surface of Ru tiny sub-nanoclusters (Co 1 Ru TCs). 43 According to the EPR spectra, the g value (2.56) of Co 1 Ru TCs could be ascribed to the unpaired electron in the orbital of Co II and Ru III . To explore the effect of electronic interaction between the atomically dispersed Co and Ru clusters, dual atomically dispersed Co and Ru (denoted as Co 1 Ru DAs) were also prepared.…”
Section: Other Applicable Characterization Techniquesmentioning
confidence: 98%
“…For example, Jiang et al reported a new strategy by integrating vacuum-freeze-drying and high-temperature pyrolysis technologies to design atomically dispersed Co deposits onto the surface of Ru clusters. 43 Cheng et al developed a universal and facile room temperature impregnation strategy to construct a Ru atomically dispersed catalyst with Ru-C 5 single atoms and Ru oxide nanoclusters ($1.5 nm), which could also be extended to prepare Ir, Rh, Pt, Au, and Mo atomically dispersed catalysts. 34 In addition, atomically dispersed metal sites on carbon, especially those with M-N-C coordination, have demonstrated excellent catalytic activities both experimentally and theoretically.…”
Section: Single Atomic Site-clusters (Saccs)mentioning
confidence: 99%
“…Furthermore, atomically dispersed Co atom anchored on subnanometer Ru cluster (Co 1 Ru TC) catalyst was developed to overcome the scaling relation and enhance NH 3 synthesis (Figure 6). [ 7 ] The special structure of this catalyst generates a spatial effect and induces strong interactions between Ru and Co, resulting in the simultaneous generation of high‐unoccupied Co 3d orbitals and obvious upshifting of Ru d‐band center. As a consequence, the activation energy of N 2 was lowered via strong electron “σ‐donation and π‐backdonation” between Ru and N 2 molecules.…”
Section: Synthesis Of Ammoniamentioning
confidence: 99%
“…Thus, we could propose a “zero‐carbon” circular economy roadmap by a “renewable energy‐green hydrogen‐green ammonia‐hydrogen energy” route, as shown in Figure 1. [ 6‐7 ] The key is to develop environmentally friendly, and energy‐saving technologies of NH 3 synthesis and utilization as the substitute to avoid aggravating the consumption of fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Because the valence electrons close to the Fermi level mainly contribute to the d states, the shift of valence band toward Fermi levels implies the upward shift of 5d-band center from Pt-b1 to Pt-b6. [39][40][41][42] Moreover, quasi in situ XPS measurements were conducted to trace the evolution of Pt electronic structure in Figures S48 and 5c. Obviously, both the binding energy and percentage of Pt species remain almost unchanged until the reaction temperature reaches 150 °C, while further raising temperature results in the partial oxidation and reduction of Pt for CO-TOX and CO-PROX, owing to the oxidized and reduced atmosphere, respectively, which were further verified by the in situ ultraviolet-visible (UV/Vis) spectra in Figures S49 and S50.…”
Section: Mechanistic Understanding Of Co Poisoning In Co-tox and Co-proxmentioning
confidence: 99%